2012
DOI: 10.1590/s0031-10492012001100001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuation in the population of Harmonia axyridis (Pallas, 1773) (Coleoptera: Coccinellidae) and co-occurrence with other Coccinellids in the Federal District of Brazil

Abstract: The multicolored Asian lady beetle, Harmonia axyridis (Pallas, 1773), was first recorded in Brazil in 2002 in Paraná state and subsequently observed in Santa Catarina, Rio Grande do Sul and Minas Gerais. This species can spread to new areas and become dominant in the local community, reducing the density and diversity of native species, mainly Coccinellidae. The objective of this work was to record for the first time the occurrence of H. axyridis in the Federal District and its co-occurrence with other Coccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
8
1
2
Order By: Relevance
“…Togni et al (2010) observed that monoculture of tomato (variety Pollyana) presented lower abundance and richness of natural enemy species (among them H. convergens and E. connexa) than the intercropping of tomato with coriander (variety Verdão) in an experiment conducted in an organic production site in Brasília, DF. Harterreiten- Souza et al (2012) observed greater richness of ladybeetle species (S = 9) in tomato crops than that observed in the current research; however, they collected specimens in tomato intercropped with coriander and other cultures. These authors also observed that ladybeetle species prevailed in this system (H. convergens).…”
Section: Experiments Conducted Bycontrasting
confidence: 81%
“…Togni et al (2010) observed that monoculture of tomato (variety Pollyana) presented lower abundance and richness of natural enemy species (among them H. convergens and E. connexa) than the intercropping of tomato with coriander (variety Verdão) in an experiment conducted in an organic production site in Brasília, DF. Harterreiten- Souza et al (2012) observed greater richness of ladybeetle species (S = 9) in tomato crops than that observed in the current research; however, they collected specimens in tomato intercropped with coriander and other cultures. These authors also observed that ladybeetle species prevailed in this system (H. convergens).…”
Section: Experiments Conducted Bycontrasting
confidence: 81%
“…In the same municipalities, Martins et al (2009) collected H. axyridis associated with potential prey species of aphids, scales, and psyllids that may be alternate prey sources, although most of the prey species were aphids. Harmonia axyridis was recorded in the states of São Paulo, Minas Gerais, and Goiás (Harterreiten-Souza et al 2012).…”
Section: Coleopteramentioning
confidence: 99%
“…Multiple researchers have warned that Ha. axyridis could destabilise local coccinellid communities in Brazil (Arruda Filho et al, 2009; Harterreiten‐Souza et al, 2012; Koch et al, 2006; Martins et al, 2009; Milléo et al, 2008; Rezende et al, 2010), but such an evaluation has yet to be done.…”
Section: Introductionmentioning
confidence: 99%